Prevalence of Hyperuricemia at a Tertiary Care Centre of Jumla, Nepal: A Retrospective Study - Shah, Tirtha Narayan; Rain, Abdullah; Prasad, Ram Jiban; Thakur, Umeshwar Prasad; Sah, Navin Kumar (Medical Journal of Eastern Nepal, 2023)
Background: Purines after its metabolism, gives rise to the formation of uric acid as an end product. More than 70% of its excretion is done by the renal system and lesser portion by intestinal and biliary system. Hyperuricemia is caused by the abnormalities in serum uric acid (SUA) metabolism and its impairment in renal function leading to the urate retention.Methods: Observational descriptive cross sectional study (retrospective chart review) done from 16th July 2021 to 15th July 2022 to determine the prevalence of hyperuricemia. The data entered in Microsoft Excel 2007 and analyzed in SPSS (statistical package for social sciences) version 16.Results: In this study, total participants were 1491 of which male was 553 (37.08%), and female was 938 (62.91%). Prevalence of hyperuricemia was 9.99% in the total population. 16.09% male and 6.39% female population were hyperuricemic.Conclusions: Besides various factors of the health hazards, hyperuricemia is also one of them and sometimes may go undiagnosed. Timely diagnosis and its treatment may protect against cardiovascular events, hypertension, renal disorders, etc.